My hero academia Volume 24 All it takes is one bad day - Horikoshi, Kohei 1986-; Cook, Caleb D.; Hunt, John 1972- (San Francisco, CA VIZ Media, LLC, 2020)
"What would the world be like if 80 percent of the population manifested superpowers called 'Quirks'? Heroes and villains would be battling it out everywhere! Being a hero would mean learning to use your power, but where would you go to study? The Hero Academy of course! But what would you do if you were one of the 20 percent who were born Quirkless? Middle school student Izuku Midoriya wants to be a hero more than anything, but he hasn't got an ounce of power in him. With no chance of ever getting into the prestigious U.A. High School for budding heroes, his life is looking more and more like a dead end. Then an encounter with All Might, the greatest hero of them all, gives him a chance to change his destiny ... A new player emerges in the underground world of villains in the form of the Meta Liberation Army. Led by the CEO of the Detnerat Corporation, the MLA is preparing for a new metahuman revolution. In their eyes, the League of Villains is an obstacle to be removed, but Tomura and his band of miscreants aren't about to go down quietly. It's army versus league in all-out war, and dominance must be established."--Provided by publisher
Translated from the Japanese.
Translation of: Boku no hiiro akademia. 24.
"First published in Japan in 2014 by SHUEISHA Inc., Tokyo."--Page opposite title page
Reads from right to left.
Parental advisory: "[R]ecommended for ages 13 and up. This volume contains fantasy violence"--Page opposite title page
On the title page, the word 'hero' is crossed out and replaced with the word 'villain'.
Keywords: High school students -- Japan -- Comic books, strips, etc; High schools -- Japan -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Ability -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Young Adult Fiction -- Comics & Graphic Novels -- Manga; Young Adult Fiction -- Comics & Graphic Novels -- Superheroes; Heroes and heroines -- Fiction; Young adult fiction; Science fiction comics; superhero comics; adventure story comics; Graphic novels; Action and adventure comics